Effectiveness of Practicum Learning with Discovery Learning Model in Improving 4C Skills of Students - Firdiawan Ekaputra (EduLine: Journal of Education and Learning Innovation, 2024)
Chemistry learning is learning that is closely related to practicum activities, so that in chemistry learning is very capable of facilitating the development of student knowledge and skills. Students' skills in collaborating in practicum activities, creativity and critical thinking skills in solving problems that are still relatively low must get serious attention in improving student skills in facing the challenges of the 21st century. The purpose of this study is to evaluate the efficacy of using the discovery learning paradigm in practicum learning to enhance 4C abilities. A total of 26 students from the Jambi University Chemistry Education Study Program who enrolled in the R-002 class inorganic chemistry practicum during the 2022–2023 academic year served as the sample for this study. This study employs an experimental design using a pretest-posttest model for a single group. A questionnaire was utilized in this study to gather information on the 4C competencies of the students. The paired samples t test was then used to evaluate the collected data. According to the study's findings, practical learning significantly improves 4C skills using a discovery learning paradigm.